Resin composition and sheet molding compound

The resin composition with inorganic particles and a resin, engineered to have specific mechanical properties, addresses the challenge of dimensional stability in semiconductor sealing members under repeated heating, achieving effective suppression of dimensional changes and maintaining mechanical strength.

JP2025060436APending Publication Date: 2025-04-10SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024155261
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-09
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

The miniaturization of semiconductor devices and narrowing of wiring pitch have led to strict requirements for the sealing member to maintain dimensions despite repeated heating, as semiconductor devices undergo high temperatures due to current and other factors, causing significant dimensional changes in the sealing member.

Method used

A resin composition containing inorganic particles and a resin, specifically designed to have a fracture stress greater than 41.2MPa and absorbed energy up to breakage of more than 0.314 MPa, which suppresses dimensional changes when repeatedly heated, and is formulated into a sheet molding compound.

Benefits of technology

The resin composition effectively suppresses dimensional changes when repeatedly heated, enhancing the dimensional stability of the sealing member against external energy, such as heat, while maintaining mechanical strength and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060436000005
    Figure 2025060436000005
  • Figure 2025060436000001
    Figure 2025060436000001
  • Figure 2025060436000002
    Figure 2025060436000002
Patent Text Reader

Abstract

To provide a resin composition comprising inorganic particles and a resin, the resin composition being capable of suppressing dimensional changes when repeatedly heated.SOLUTION: A resin composition includes inorganic particles and a resin, has a fracture stress of more than 41.2 MPa, and has an absorption energy up to the fracture of more than 0.314 MPa.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to resin compositions and sheet molding compounds. [Background technology]

[0002] Heat generated by passing electricity through electronic components is likely to adversely affect the performance of the electronic components, so it is desirable to dissipate the heat quickly. Therefore, for example, it is desirable for a member constituting a semiconductor sealing member surrounding an IC chip to exhibit high thermal conductivity for heat dissipation. The sealing member may generally contain inorganic particles and resin, as described in Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-200478 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, with the miniaturization of semiconductor devices and the narrowing of wiring pitches, strict requirements have been placed on the sealing member with respect to dimensional change due to heat. In particular, since semiconductor devices can be repeatedly exposed to high temperatures due to current flow, etc., it has become problematic that the dimensions of the sealing member change significantly when repeatedly heated. In the conventional technology as described in Patent Document 1, suppression of dimensional changes caused by repeated heating has not been considered.

[0005] In view of this situation, one embodiment of the present invention aims to provide a resin composition containing inorganic particles and a resin, which is capable of suppressing dimensional change when repeatedly heated. Another embodiment of the present invention has an object to provide a sheet-shaped composition (sheet molding compound) comprising such a resin composition. [Means for solving the problem]

[0006] Aspect 1 of the present invention is Contains inorganic particles and a resin, The breaking stress is more than 41.2 MPa, The resin composition has an absorbed energy of more than 0.314 MPa until breakage.

[0007] Aspect 2 of the present invention is The resin composition according to aspect 1, wherein a correlation coefficient when a stress-strain curve up to break is linearly approximated exceeds 0.9765.

[0008] Aspect 3 of the present invention is Alpha radiation dose is 0.022cph / cm 2 3. The resin composition according to claim 1 or 2,

[0009] A fourth aspect of the present invention is The resin composition according to any one of Aspects 1 to 3, wherein the inorganic particles have a strain at break of less than 0.113 in a particle compression test.

[0010] A fifth aspect of the present invention is The resin composition according to any one of Aspects 1 to 4, wherein the inorganic particles have a breaking strength of less than 1080 MPa in a particle compression test.

[0011] A sixth aspect of the present invention is The resin composition according to any one of Aspects 1 to 5, wherein the inorganic particles have an absorbed energy until breakage of less than 61.0 MPa in a particle compression test.

[0012] A seventh aspect of the present invention is The resin composition according to any one of Aspects 1 to 6, wherein the inorganic particles have a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.39.

[0013] Aspect 8 of the present invention is The inorganic particles have an isolated OH group count of 3.1 / nm 2 The resin composition according to any one of Aspects 1 to 7, wherein the viscosity is less than 100 μm.

[0014] A ninth aspect of the present invention is The resin composition according to any one of aspects 1 to 8 is used. A sheet molding compound having a thickness of 1000 μm or less. Effect of the Invention

[0015] According to an embodiment of the present invention, it is possible to provide a resin composition containing inorganic particles and a resin, which is capable of suppressing dimensional change when repeatedly heated, and a sheet molding compound made of the resin composition. [Brief description of the drawings]

[0016] [Figure 1] 1 is an example of a plot of strain-strength (MPa) obtained by carrying out a compression test on inorganic particles in accordance with JIS R1639-5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present inventors have conducted extensive research to realize a resin composition capable of suppressing dimensional changes when repeatedly heated. As a result, it has been found that by controlling the breaking stress and the absorbed energy until breakage of a resin composition containing inorganic particles and a resin to be greater than a predetermined value, it is possible to suppress dimensional changes when repeatedly heated. This is believed to be because, by controlling the breaking stress of the resin composition to be greater than a predetermined value, the resin composition is less likely to break, and by controlling the absorbed energy until breakage of the resin composition to be greater than a predetermined value, the toughness is improved and shape recovery performance can be ensured, resulting in improved dimensional stability against external energy such as heat.

[0018] The resin composition according to this embodiment and the sheet molding compound (SMC) made of the resin composition will be described below. In this specification, the term "resin composition" is intended to include all of the resin compositions in the liquid state before the resin in the resin composition is cured, the semi-cured state (B stage) in which the resin is semi-cured, and the cured state (C stage) in which the resin is completely cured. Here, the "liquid state" includes compositions in which the resin composition has fluidity, such as resin compositions containing a solvent described below. The "semi-cured state" refers to a state in which the resin composition is cured to an extent that it can be handled as a solid, but is not completely cured, and therefore the surface of the resin composition is sticky. The "cured state" refers to a state in which the resin composition can be handled as a solid and has almost no stickiness on the surface.

[0019] [Resin composition] The resin composition according to the present embodiment contains inorganic particles and a resin, has a breaking stress of more than 41.2 MPa, and absorbs energy to break of more than 0.314 MPa, which can suppress dimensional changes when repeatedly heated.

[0020] The rupture stress of the resin composition is measured in a semi-cured or cured state. The rupture stress of the resin composition is preferably 50.0 MPa or more, more preferably 60.0 MPa or more, and even more preferably 65.0 MPa or more. In particular, it is preferable that the rupture stress of the cured resin composition is more than 41.2 MPa, 50.0 MPa or more, 60.0 MPa or more, or 65.0 MPa or more, in that order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The rupture stress of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The rupture stress of the resin composition in the semi-cured state and the cured state can be increased by adjusting the content of inorganic particles and the curing conditions. Usually, the rupture stress of the cured resin composition is higher than that of the semi-cured state.

[0021] The absorption energy of the resin composition until breakage is measured in a semi-cured or cured state. The absorption energy of the resin composition until breakage is preferably 0.400 MPa or more, more preferably 0.500 MPa or more, and even more preferably 0.600 MPa or more. In particular, it is preferable that the absorption energy of the resin composition after curing is more than 0.314 MPa, 0.400 MPa or more, 0.500 MPa or more, or 0.600 MPa or more in this order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The absorption energy of the resin composition until breakage can be calculated from the area surrounded by the stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The absorption energy of the resin composition until breakage in the semi-cured and cured states can be increased by adjusting the content of inorganic particles and the curing conditions. Usually, the absorption energy until breakage is higher in the cured state than in the semi-cured state.

[0022] The stress-strain curve of the resin composition until breakage is measured with the resin composition in a semi-cured or cured state. The correlation coefficient when the stress-strain curve of the resin composition until breakage is linearly approximated is preferably greater than 0.9765. A large correlation coefficient indicates that the resin composition stretches uniformly, and may mean that, for example, inorganic particles are not aggregated with each other and inorganic particles are uniformly dispersed in the resin. In that case, moderate interaction between the particles and the resin is easily performed, and dimensional stability against external energy such as heat is easily ensured. The correlation coefficient is preferably 0.9780 or more, more preferably 0.9795 or more. In particular, it is preferable that the correlation coefficient when the stress-strain curve of the cured resin composition until breakage is linearly approximated is greater than 0.9765, 0.9780 or more, or 0.9795 or more. The upper limit of the correlation coefficient is 1.0000.

[0023] The alpha dose of the resin composition is 0.022 cph / cm 2It is preferable that the dose of α-rays is less than 0.020 cph / cm. This is because semiconductor devices are easily affected by α-rays, and malfunctions (soft errors) caused by α-rays are likely to become a problem. Furthermore, if the dose of α-rays is low, damage to the semiconductor element is small, adhesion at the interface between the resin composition and the element is easily maintained, and deformation due to thermal history is easily suppressed. The α-ray dose of the resin composition is preferably 0.020 cph / cm. 2 or less, more preferably 0.015 cph / cm 2 Less than 0.005 cph / cm, more preferably 0.005 cph / cm 2 Less than 0.002 cph / cm is particularly preferable. 2 In particular, the alpha radiation dose of the cured resin composition is 0.022 cph / cm 2 Less than 0.020cph / cm 2 Below, 0.015cph / cm 2 Below, 0.005cph / cm 2 Less than or equal to 0.002cph / cm 2 The lower the alpha dose of the resin composition, the more preferable. The lower limit is preferably 0.000 cph / cm 2 The alpha radiation amount of the resin composition is measured in a semi-cured or cured state using an alpha radiation measuring device (e.g., Model 1950 manufactured by Alpha Sciences, Inc.). The measurement area of ​​the sample is 1000 cm. 2 The measurement time is 99 hours, and the counting gas used is PR-10 gas (Ar 90%, CH4 10%).

[0024] The elastic modulus of the resin composition is measured in the resin composition in a semi-cured or cured state. The elastic modulus (tensile elastic modulus) of the resin composition is preferably 2.0 GPa or more. The elastic modulus of the resin composition is more preferably 3.0 GPa or more, even more preferably 4.0 GPa or more, particularly preferably 5.0 GPa or more, even more particularly preferably 6.0 GPa or more, and most preferably 7.0 GPa or more. In particular, the elastic modulus of the resin composition after curing is preferably 2.0 GPa or more, and a sealing member that can withstand deformation under general use conditions can be formed. The elastic modulus of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The elastic modulus of the resin composition in the semi-cured state and the cured state can be increased by adjusting the content of inorganic particles and the curing conditions. Usually, the elastic modulus of the resin composition in the cured state is higher than that in the semi-cured state.

[0025] As the inorganic particles, ceramics such as silica, alumina, aluminum nitride, boron nitride, silicon nitride, and silicon carbide are preferred. In particular, particles made of inorganic materials with high thermal conductivity are preferred, for example, particles made of inorganic materials with thermal conductivity of 15 W / mK or more are preferred. As such inorganic materials, ceramics such as alumina, aluminum nitride, boron nitride, silicon nitride, and silicon carbide are suitable. The inorganic particles are preferably ceramic particles. Since ceramics have high thermal conductivity, the use of ceramic particles can improve the heat dissipation performance of the resin composition. In addition, when insulating ceramics are used as inorganic particles, short circuits in the semiconductor device can be suppressed. Therefore, it is more preferable that the inorganic particles are insulating ceramic particles, and more specifically, it is more preferable that the inorganic particles are alumina, aluminum nitride, boron nitride, and silicon nitride. Among them, alumina is even more preferred because of its low price. Furthermore, it is preferable that the inorganic particles include α-alumina particles. Alpha-alumina is expected to have the effect of reducing the amount of alpha rays emitted from the inorganic particles, and the presence of alpha-alumina particles in the inorganic particles can result in an improved effect of suppressing the amount of alpha rays emitted from the resin composition.

[0026] The resin composition according to this embodiment can suppress dimensional changes when repeatedly heated, for example, even when using low-strength particles that are relatively easy to manufacture or obtain (low-cost). This satisfies the above-mentioned specific requirements discovered by the inventors regarding the breaking stress and the absorbed energy until breakage. For example, even if the resin composition according to the present embodiment contains inorganic particles with small strain at break in a particle compression test, the dimensional change when repeatedly heated can be suppressed by satisfying the above-mentioned predetermined requirements. That is, when the resin composition according to the present embodiment contains inorganic particles with a strain at break of less than 0.113 in a particle compression test, the effect of the present invention becomes more prominent, when the resin composition contains inorganic particles with the strain of 0.110 or less, the effect of the present invention becomes even more prominent, and when the resin composition contains inorganic particles with the strain of 0.100 or less, the effect of the present invention becomes even more prominent. The strain is not particularly limited in terms of the lower limit, but may be, for example, 0.050 or more.

[0027] The strain at the time of fracture of the inorganic particles is measured as follows. First, a compression test of inorganic particles is performed in accordance with JIS R1639-5 to obtain a plot of displacement vs. test force. The displacement in the plot is converted to strain based on the following formula (1), and the test force in the plot is converted to strength based on the following formula (2) to obtain a plot of strain vs. strength (MPa) as shown in Figure 1. Strain = displacement [μm] / D[μm] (1) Strength [MPa] = 2.48 × test force [N] / (π × D 2 ) · · · (2) Here, D [μm] is the average value of the major axis and minor axis of the inorganic particles to be tested. The major axis and minor axis can be measured by observation with an optical microscope.

[0028] In Fig. 1, when there is one region with a constant slope, the minimum displacement at which the displacement exceeds 0 and the slope is constant is taken as the breaking point P1. The strain d1 at the breaking point P1 is taken as the strain at the time of breaking in the particle compression test. When there are multiple regions with a constant slope, the starting point of the region where the difference in strain between the end point and the starting point of the region is the largest is taken as the breaking point P1. In addition, the compression test of the inorganic particles in the resin composition can be performed by removing the resin contained in the resin composition, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to thermally decompose the resin, isolating only the inorganic particles, and using the inorganic particles.

[0029] Even if the resin composition according to the present embodiment contains inorganic particles having a low breaking strength in a particle compression test, the resin composition according to the present embodiment can suppress the dimensional change when repeatedly heated by satisfying the above-mentioned predetermined requirements. That is, when the resin composition according to the present embodiment contains inorganic particles having a breaking strength of less than 1080 MPa in a particle compression test, the effect of the present invention becomes more prominent, when the resin composition contains inorganic particles having a breaking strength of 1050 MPa or less, the effect of the present invention becomes even more prominent, and when the resin composition contains inorganic particles having a breaking strength of 1000 MPa or less, the effect of the present invention becomes even more prominent. The breaking strength is not particularly limited in terms of the lower limit, but may be, for example, 500 MPa or more.

[0030] The breaking strength of the inorganic particles is measured as follows. A compression test of inorganic particles is carried out in accordance with JIS R1639-5 to obtain a plot of strain-strength (MPa) as shown in Figure 1. In the plot, the strength at breaking point P1 is taken as breaking strength s1 (MPa).

[0031] Even if the resin composition according to the present embodiment contains inorganic particles with low absorption energy to breakage in a particle compression test, the dimensional change when repeatedly heated can be suppressed by satisfying the above-mentioned predetermined requirements. That is, when the resin composition according to the present embodiment contains inorganic particles with absorption energy to breakage of less than 61.0 MPa in a particle compression test, the effect of the present invention becomes more prominent, when the resin composition contains inorganic particles with absorption energy to breakage of 55.0 MPa or less, the effect of the present invention becomes even more prominent, and when the resin composition contains inorganic particles with absorption energy to breakage of 50.0 MPa or less, the effect of the present invention becomes even more prominent. The absorption energy to breakage is not particularly limited in terms of the lower limit, but may be, for example, 10.0 MPa or more.

[0032] The energy absorbed until the inorganic particles are destroyed is measured as follows. A compression test of inorganic particles is carried out in accordance with JIS R1639-5, and a plot of displacement (μm) vs. strength (MPa) is obtained as shown in Figure 1. In Figure 1, the area of ​​the region (shaded area) surrounded by the plot, the line of strength = 0 MPa, and the line of strain = d1 is calculated as the absorbed energy (MPa) until fracture.

[0033] The resin composition according to the present embodiment preferably contains inorganic particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups (i.e., "number of isolated OH groups / number of hydrogen-bonded OH groups") of less than 0.39. The smaller the number of isolated OH groups, the lower the bonding strength between particles, and as a result, the particles can be prevented from coagulating. It is more preferable to contain inorganic particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of 0.35 or less, and even more preferable to contain inorganic particles having a ratio of 0.30 or less. On the other hand, it is preferable to contain inorganic particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of 0.01 or more. This makes it easier for an appropriate interaction to occur between the particles and the resin. It is more preferable to contain inorganic particles having a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of 0.03 or more, and even more preferable to contain inorganic particles having a ratio of 0.05 or more. The inorganic particles may have OH groups on their surfaces by reacting with moisture in the air.

[0034] The resin composition according to this embodiment has an isolated OH group count of 3.1 / nm 2 It is preferable that the inorganic particles contain inorganic particles having an isolated OH group number of less than 2.8 / nm. This can suppress aggregation of particles. 2 More preferably, the number of isolated OH groups is 2.5 / nm 2 More preferably, the number of isolated OH groups is 2.0 / nm 2 It is even more preferable that the number of isolated OH groups is 1.5 / nm 2 On the other hand, it is particularly preferable that the number of isolated OH groups is less than 0.1 / nm 2 It is preferable that the resin contains inorganic particles having an isolated OH group number of 0.2 / nm or more. This facilitates appropriate interaction between the particles and the resin. 2 More preferably, the inorganic particles contain 0.3 particles / nm or more. 2 It is more preferable that the inorganic particles contain the above inorganic particles.

[0035] In this embodiment, the number of isolated OH groups and the number of hydrogen-bonded OH groups of the inorganic particles can be quantified using the measurement results by the Karl Fischer method (moisture vaporization-titration method) in accordance with the description of JIS K 0068: 2001 "Method for measuring moisture in chemical products". The moisture detected in the Karl Fischer measurement can be considered to be derived from the OH groups of the inorganic particles, and the moisture detected at a temperature of 550°C can be considered to be derived from the hydrogen-bonded OH groups, and the moisture detected at a temperature of 900°C can be considered to be derived from the isolated OH groups. The moisture detected in the Karl Fischer measurement is considered to be one water molecule formed by condensing two OH groups, and the number of OH groups can be calculated by the following formula (3). Number of OH groups [pcs / nm 2 ] = 0.0662 × (water content [ppm]) / (specific surface area of ​​inorganic particles [m 2 / g]) · · · (3)

[0036] In quantifying the number of isolated OH groups and the number of hydrogen-bonded OH groups of inorganic particles in a resin composition, first, the resin contained in the resin composition is removed, for example, by dissolving it in an organic solvent, etc., to separate only the inorganic particles. The number of isolated OH groups and the number of hydrogen-bonded OH groups can be quantified using the separated inorganic particles in the same manner as described above.

[0037] The resin composition according to this embodiment has a specific surface area of ​​0.20 m 2 It is preferable that the resin contains inorganic particles having a specific surface area of ​​0.36 m / g or more. This facilitates appropriate interaction between the particles and the resin. 2 More preferably, the inorganic particles have a specific surface area of ​​more than 0.40 m 2 More preferably, the inorganic particles have a specific surface area of ​​0.45 m / g or more. 2 It is even more preferable that the inorganic particles contain inorganic particles having a specific surface area of ​​0.55 m / g or more. 2 It is particularly preferable that the inorganic particles contain inorganic particles having a specific surface area of ​​3.00 m / g or more. 2 / g or less, preferably 2.50m 2 / g or less. In this embodiment, the specific surface area of ​​the inorganic particles is a nitrogen adsorption BET specific surface area, and is measured in accordance with JIS-Z8830 (2013). When the inorganic particles are contained in a resin composition, the resin contained in the resin composition is removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, and only the inorganic particles are separated, and the specific surface area can be measured using the inorganic particles.

[0038] By reducing the grain boundary content in the inorganic particles, it is possible to improve the shielding effect against alpha rays generated from uranium and thorium in the inorganic particles and reduce the amount of alpha rays emitted from the inorganic particles. In this embodiment, the ratio of the total length L2 of the grain boundaries to the length L1 of the outer edge (L2 / L1) is introduced as an index of the grain boundary content inside the inorganic particle. L1 and L2 are determined by observing the cross section of the inorganic particle.

[0039] When the length of the outer edge of one inorganic particle is L1 and the total length of the grain boundaries of the inorganic particle is L2, an inorganic particle with a small value of L2 / L1 is said to have a small grain boundary content and emits a low amount of α-rays. In particular, it is preferable that (L2 / L1) (%) is less than 139.1%, which can further reduce the amount of α-rays emitted when used as a filler for a resin composition. By reducing the amount of α-rays emitted from the inorganic particles, the amount of α-rays emitted from a resin composition containing the inorganic particles can also be reduced.

[0040] (L2 / L1) is preferably 120.0% or less, more preferably 100.0% or less, even more preferably 80.0% or less, even more preferably 60.0% or less, particularly preferably 52.0% or less, and most preferably 50.0% or less. The lower limit of (L2 / L1) is not particularly limited, but may be 10.0% or more, for example, 20.0% or more, 30.0% or more, 40.0% or more, or 43.0% or more. When the lower limit of L2 / L1 is within the above range, the interaction between the particles and the resin becomes easier to work, and the mechanical strength such as the breaking stress of the resin composition is easily increased. In order to control this L2 / L1 within a suitable range, single crystal raw material particles may be used.

[0041] The "total length L2 of grain boundaries" is the sum of the grain boundaries contained inside the inorganic particle, and does not include the outer edge of the inorganic particle. The total length L2 of grain boundaries is the sum of the total length L3 of grain boundaries inside the inorganic particle and the total length L4 of the inner wall of the cavity (if there is a cavity inside the inorganic particle) (i.e., L2 = L3 + L4). In addition, when inorganic particles are contained in the resin composition, the resin contained in the resin composition can be removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to thermally decompose the resin, and only the inorganic particles can be isolated, and L2 / L1 can be measured using the inorganic particles.

[0042] Inorganic particles with a sharp particle size distribution are preferred because they facilitate moderate interaction between the particles and the resin. For example, the ratio D90 / D50 of the particle size D90 (hereinafter sometimes simply referred to as "D90") of the cumulative 90% of the number of particles from the fine particle side of the cumulative particle size distribution to the particle size D50 (hereinafter sometimes simply referred to as "D50") of the cumulative 50% of the number of particles from the fine particle side of the cumulative particle size distribution is preferably 5.0 or less. D90 / D50 is more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 1.5 or less.

[0043] On the other hand, if the particle size distribution of the inorganic particles is broad to some extent, the filling property is improved by allowing small particles to enter the gaps between large particles, and more inorganic particles can be kneaded into the resin, which can increase the dimensional stability and breaking stress against external energy such as heat. Therefore, D90 / D50 is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more.

[0044] The inorganic particles preferably have a D50 of 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, even more preferably 10 μm or less, particularly preferably 5 μm or less, and most preferably 3 μm or less. By having a D50 within the above range, a resin composition suitable for miniaturizing semiconductor devices and narrowing the wiring pitch can be formed.

[0045] In this embodiment, the D90 and D50 of the inorganic particles can be determined by measuring the particle size distribution of the inorganic particles by a laser diffraction method using, for example, a laser particle size distribution measuring device such as a Microtrack MT3300EXII manufactured by Microtrack Bell Co., Ltd. The particle size of the inorganic particles in the resin composition can be measured by removing the resin contained in the resin composition, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, isolating only the inorganic particles, and using the inorganic particles.

[0046] Another method for determining the D90 and D50 of inorganic particles is a method using image analysis. The resin composition may be subjected to cross-sectional observation using an SEM, and all inorganic particles contained in a predetermined observation area (e.g., 200 μm×200 μm) may be subjected to image analysis, and the particle diameters equivalent to D90 and D50 may be calculated based on the measurement results of their particle diameters (equivalent circle diameters).

[0047] The inorganic particles preferably have a uranium content of less than 550 ppb and a thorium content of less than 10 ppb. By suppressing the uranium and thorium contents of the inorganic particles to very small amounts as described above, the amount of α-rays emitted from the inorganic particles can be reduced, and as a result, the amount of α-rays emitted from the resin composition can be suppressed. This makes it possible to suppress malfunction of the semiconductor device due to α-rays when used as an encapsulating material for the semiconductor device.

[0048] The uranium content is preferably 300 ppb or less, more preferably 100 ppb or less, even more preferably 50 ppb or less, particularly preferably 30 ppb or less, for example 10 ppb or less, or 5 ppb or less. The lower limit of the uranium content is not particularly limited, but may be 0.1 ppb or more. The thorium content is preferably 8 ppb or less, more preferably 5 ppb or less, and particularly preferably 2 ppb or less. The lower limit of the thorium content is not particularly limited, but may be 0.1 ppb or more. The uranium and thorium contents can be measured using inductively coupled plasma mass spectrometry (ICP-MS). In addition, when inorganic particles are contained in the resin composition, the resin contained in the resin composition can be removed, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to thermally decompose the resin, and only the inorganic particles can be isolated, and the uranium content and thorium content can be measured using the inorganic particles.

[0049] The blending ratio of the inorganic particles is preferably in the order of 5 to 75 volume% of resin, 95 to 25 volume% of inorganic particles, or 8 to 50 volume% of resin, 92 to 50 volume% of inorganic particles, or 10 to 40 volume% of resin, 90 to 60 volume% of inorganic particles, 12 to 40 volume% of resin, and 88 to 60 volume% of inorganic particles, in the total resin composition. This makes it easier to control the breaking stress and the absorbed energy until breaking of the resin composition to a desired value. In addition, in the semi-cured and cured resin compositions, the total ratio of the resin and the inorganic particles to the total resin composition is preferably 60 volume% or more, more preferably 70 volume% or more, and even more preferably 80 volume% or more. In addition, in the semi-cured and cured resin compositions, the ratio of the solid content to the total resin composition is preferably 80 volume% or more, more preferably 90 volume% or more, and even more preferably 95 volume% or more. The solid content of a resin composition refers to what remains as a solid when the resin composition is heated, excluding, for example, the solvent and other components that volatilize upon heating. On the other hand, even if a component is liquid at 25°C, if it is incorporated into the solid content of the resin composition when heated, it is included in the solid content. The proportion of the solid content can be determined, for example, by determining the amount of solvent in the resin composition and subtracting it from the total. The amount of solvent in the resin composition can be measured, for example, by the following method. After measuring the mass W1 (g) of the resin composition, the sample is heated at 150°C for 10 minutes using a total exhaust oven to evaporate all the solvent contained in the sample, and then the sample is left at room temperature for 5 minutes to return to room temperature, and the mass W2 (g) of the sample after heating is measured. The amount of solvent in the resin composition can be determined by subtracting W2 (g) from W1 (g).

[0050] The resin composition of the present invention has a small dimensional change when repeatedly heated, and has excellent dimensional stability. In the present invention, the dimensional stability can be evaluated by measuring the CTE twice and then calculating the CTE change rate from the following formula (4). The CTE change rate is preferably less than 8.5, more preferably 8.4 or less, even more preferably 8.0 or less, even more preferably 7.0 or less, and particularly preferably 6.0 or less. CTE change rate (%) = (CTE at first measurement – ​​CTE at second measurement) / (CTE at first measurement) × 100 (4)

[0051] The resin used in the resin composition preferably contains one or more selected from the group consisting of epoxy resins and thermoplastic polyimides, and more preferably contains an epoxy resin. Preferred epoxy resins include mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins. The mesogenic epoxy resin is an epoxy resin having a mesogenic group, and is preferably a resin that exhibits a phase transition temperature in the temperature range of 100°C to 200°C to be sealed and exhibits liquid crystallinity. The resin contained in the resin composition may contain one or more epoxy resins. That is, the resin contained in the resin composition may contain one or more epoxy resins selected from the group consisting of mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins, and may further contain a thermoplastic polyimide. These resins are expected to have an effect of shielding alpha rays that may be emitted from inorganic particles. Furthermore, by using these resins, it becomes easier to obtain a resin composition having high dimensional stability against external energy such as heat.

[0052] Furthermore, these resin compositions may be appropriately mixed with known additives such as plasticizers, curing agents, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weather resistance agents, antiblocking agents, antistatic agents, leveling agents, and release agents, either singly or in combination, as long as the effects of the invention are not impaired. In addition, as an embodiment of the present application, the resin composition (particularly, a resin composition in a liquid state or a semi-cured state) may contain a solvent, and when the resin composition contains a solvent, it is easy to flow, can be easily deformed to match the fine structure of the IC chip and the substrate, and can seal the dense structure without gaps. As the solvent, a known solvent can be used, and is not limited as long as it can dissolve the resin, and examples of the solvent include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, amine-based solvents, amide-based solvents, halogen-based solvents, hydrocarbon-based solvents, and nitrile-based solvents. Ketone-based solvents and ester-based solvents are preferred from the viewpoint of being good solvents for epoxy resins and excellent coating properties of the resulting resin composition.

[0053] In a preferred embodiment of the present invention, the resin composition includes inorganic particles, an epoxy resin, a solvent, and a hardener, such as an amine-based hardener such as 4,4-diaminodiphenylmethane.

[0054] A method for producing the resin composition will be described. A resin composition can be obtained by mixing inorganic particles and a resin using a commonly used known method. For example, when the resin is liquid (such as liquid epoxy resin), the liquid resin, inorganic particles, and a curing agent are mixed, and then cured with heat or ultraviolet light to obtain a resin composition. Known curing agents, mixing methods, and curing methods can be used. On the other hand, when the resin is solid (such as epoxy resin, polyolefin resin, acrylic resin, etc.), the inorganic particles and the resin are mixed, and then kneaded by a known method such as melt kneading, or the resin, inorganic particles, and a curing agent are dissolved and mixed in a solvent to obtain a desired resin composition. The resin composition may contain a solvent.

[0055] The resin composition according to this embodiment includes a resin composition in all states, including a liquid state before the resin in the resin composition is cured, a semi-cured state (B stage) in which the resin is semi-cured, and a cured state (C stage) in which the resin is completely cured. The resin composition in a liquid state includes a compound in which alumina powder and a resin are mixed in a predetermined mixing ratio, a mixture obtained by mixing the compound, and a molded product obtained by molding the mixture. The semi-cured resin composition includes a resin composition obtained by semi-curing a resin contained in a mixture or a molded product. The cured resin composition includes a resin composition obtained by completely curing a resin contained in a mixture, a molded product, or a semi-cured product.

[0056] The method for producing inorganic particles according to this embodiment will be described by taking a method for producing alumina particles as an example.

[0057] First, the raw material alumina is produced by a known method, such as the Bayer method, the ammonium alum method, the ammonium aluminum carbonate hydroxide method (AACH method), the solvent extraction method, the organoaluminum hydrolysis method (aluminum alkoxide method), the CZ method, the Verneuil method, the chiroporous method, the Bridgman method, the EFG method, or other melt growth methods.

[0058] In the case of the Bayer process, raw alumina can be produced by calcining aluminum hydroxide obtained from bauxite. In addition, the ammonium alum process, the AACH process, the solvent extraction process, and the aluminum alkoxide process are preferable because they can produce high-purity raw alumina with low uranium and thorium contents. If raw alumina produced by these methods, in which the uranium content is suppressed to, for example, less than 550 ppb and the thorium content is suppressed to, for example, less than 10 mass ppb, is used for the production of alumina particles, it is preferable because alumina particles with reduced uranium and thorium contents can be obtained.

[0059] In order to easily obtain alumina particles of a desired size by flame melting, the raw alumina is pulverized to obtain an alumina raw powder to be subjected to flame melting. The raw alumina can be pulverized by a known method such as a vibration mill, a bead mill, a ball mill, or a jet mill, and may be pulverized in either a dry or wet state.

[0060] In the above-mentioned pulverization, a surface protective agent may be used. The surface protective agent may not only protect the surface of the alumina raw material powder after pulverization, but also have the function of inactivating the surface of the alumina raw material powder. The surface protective agent can reduce the aggregation of the alumina raw material powders themselves due to its function of inactivating the surface, and is therefore suitable for obtaining alumina particles of a desired particle size after flame fusion using raw material alumina with a high BET specific surface area that is prone to aggregation. Suitable surface protective agents include, for example, monohydric alcohols such as methanol, ethanol, 1-propanol, and 2-propanol; glycols such as ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol; amines such as triethanolamine; and higher fatty acids such as palmitic acid, stearic acid, and oleic acid. Of these surface protective agents, one type may be used alone, or two or more types may be used in combination. Of these, glycols are preferred, and in particular, one or more types of ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol are preferred.

[0061] For example, polyethylene glycol and polypropylene glycol, which are preferably used as surface protective agents, are not particularly limited in terms of their molecular weight, but liquid ones with an average molecular weight of about 200 to 600 are preferred for ease of addition.

[0062] The amount of the surface protective agent added is preferably 0.01 parts by mass or more in order to fully exert the effect of the surface protective agent when the raw material alumina is taken as 100 parts by mass, and is preferably 10 parts by mass or less because the effect of the surface protective agent becomes saturated if the amount of the surface protective agent added is too large. The amount of the surface protective agent added is more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0063] Here, the flame fusion method will be described. The flame fusion method is a method in which the raw material of inorganic particles (raw alumina in the case of alumina particles) is sprayed into a flame, turned into droplets, and then cooled and solidified. By using the flame fusion method, inorganic particles can be obtained while maintaining the particle diameter of the inorganic particle raw material. In the flame fusion method, the temperature of the flame fusion furnace is preferably 1000°C or higher. In particular, by setting the raw material supply rate to 50 kg / h or less, preferably 10 kg / h or less in the flame fusion method, it becomes easier to suppress aggregation between particles, and it becomes easier to create an appropriate interaction between the particles and the resin, and as a result, it becomes easier to obtain a resin composition that satisfies the above-mentioned specified requirements.

[0064] After the flame melting, the alumina particles are collected by a cyclone and / or a bag filter and classified to obtain alumina particles having desired properties.

[0065] The number of isolated OH groups of the alumina particles can be controlled by the conditions of the manufacturing method of the raw alumina, the pulverization method, and the flame fusion method, but can also be controlled by immersing the obtained alumina particles in an acidic solution such as hydrochloric acid. The type of acidic solution used during immersion is preferably hydrochloric acid because of the ease of concentration adjustment. The concentration of the acidic solution is preferably adjusted to 1M to 12M, more preferably 1M to 10M, and particularly preferably 2M to 5M. The mass ratio during immersion is preferably alumina particles:acidic solution of 1:2 to 1:10. The immersion time is preferably 5 hours or more. During immersion, heating may be performed appropriately to shorten the immersion time, for example, heating may be performed to 50 to 90°C. After immersion, washing and drying are preferably performed.

[0066] [Sheet Molding Compound (SMC)] The resin composition according to the embodiment can be used to provide a sheet molding compound (SMC). The SMC is a resin composition molded into a sheet. The SMC is preferably one that has flowability when heated and pressurized, and may be in a semi-cured state. The thickness of the SMC is preferably 1000 μm or less, and when incorporated into a semiconductor device, the semiconductor device can be made smaller and lighter, and when sealing an IC chip, the sealing performance can be improved. The thickness is more preferably 800 μm or less, even more preferably 600 μm, even more preferably 500 μm or less, particularly preferably 400 μm or less, and particularly preferably 300 μm or less. The lower limit of the thickness is not particularly limited, but from the viewpoint of the dimensions of SMCs generally used and improving the sealing performance of IC chips, it may be, for example, 10 μm or more, 50 μm or more, or even 100 μm or more, or 150 μm or more.

[0067] The SMC can be produced by a known method. As an example, an uncured resin composition is applied onto a substrate, a protective film is placed thereon, and the resin composition is semi-cured. As another example, an uncured resin composition containing a solvent is applied onto a substrate, the solvent is removed from the resin composition by drying or the like, and then a protective film is placed. When using the SMC, the protective film is peeled off, the SMC is pressed against a wafer or the like, the substrate is removed, and the SMC is post-cured.

[0068] The resin composition and SMC according to this embodiment are suitable as sealing materials for semiconductor elements because they can suppress dimensional changes when repeatedly heated. EXAMPLES

[0069] [Preparation of inorganic particles] The inorganic particles (A to C) used in the resin compositions of Samples No. 1 to 4 were prepared as follows.

[0070] (Inorganic particles A and B used in samples No. 1 to 3) As inorganic particles, the following inorganic particles A (alumina particles, used in Sample No. 3) and inorganic particles B (alumina particles, used in Samples No. 1 and 2) were prepared.

[0071] As the raw material for inorganic particles, γ-alumina obtained by the ammonium alum method (the average particle size of the primary particles calculated from the value of the BET specific surface area below is 13 nm) was used. The BET specific surface area of ​​this γ-alumina by the nitrogen adsorption method is 120 m 2 Before pulverization, 4% by mass of propylene glycol was added as a surface protective agent to the raw alumina and mixed.

[0072] Next, the alumina was processed using a jet mill pulverizer (horizontal jet mill pulverizer PJM-280SP manufactured by Japan Pneumatic Mfg. Co., Ltd.) under the conditions of a feed rate of the raw alumina of 30 kg / h and a gauge pressure of the air supply port during pulverization of 0.5 MPa, to obtain an alumina raw powder with an average secondary particle size of approximately 2 μm.

[0073] The obtained alumina raw material powder was put into a flame melting furnace and melted to obtain spherical alumina particles. The atmospheric temperature in the flame melting furnace was set to 1250°C, and the raw material supply rate was set to 5 kg / h. The obtained alumina particles were collected by a cyclone and classified by cyclone classification to remove particles of 20 μm or more to obtain inorganic particles A (D50=5.1 μm, used for sample No. 3). Furthermore, particles of 10 μm or more were removed to obtain inorganic particles B (D50=2.3 μm, used for sample Nos. 1 and 2).

[0074] (Alumina particle C used in sample No. 4) For sample No. 4, alumina particles (inorganic particles C) of DAW05 manufactured by Denka were used.

[0075] The inorganic particles used in each sample were subjected to the following measurements.

[0076] [Distortion of inorganic particles upon destruction] A compression test of inorganic particles was conducted in accordance with JIS R1639-5 to obtain a plot of displacement vs. test force. The displacement in the plot was converted to strain based on the following formula (1), and the test force in the plot was converted to strength based on the following formula (2) to obtain a plot of strain vs. strength. Strain = Displacement [m] / D [m] (1) Strength [MPa] = 2.48 × test force [N] / (π × D 2 ) · · · (2) Here, D [m] is the average value of the major axis and the minor axis of the inorganic particles to be tested, which were measured by observation with an optical microscope. In the case where there is one region with a constant slope in the strain-strength plot, the minimum displacement where the displacement exceeds 0 and the slope is constant was taken as the breaking point P1, and the strain d1 at the breaking point P1 was taken as the strain at the time of breaking in the compression test of the particle. Note that, in the case where there are multiple regions with a constant slope, the starting point of the region where the difference in strain between the end point and the starting point of the region is the largest was taken as the breaking point P1.

[0077] [Breaking strength of inorganic particles] In the above strain-strength plot, the strength at the breaking point P1 was taken as the breaking strength s1 (MPa) of the inorganic particles.

[0078] [Energy absorbed until inorganic particles break] In the above strain-strength plot, the area of ​​the region (shaded area) surrounded by the plot, the line of strength=0 MPa, and the line of strain=d1 was calculated as the absorbed energy (MPa) until the inorganic particles broke.

[0079] [Number of isolated OH groups and hydrogen-bonded OH groups on inorganic particles] The number of isolated OH groups and hydrogen-bonded OH groups of inorganic particles was quantified using the results of measurement by the Karl Fischer method (moisture vaporization-titration method) in accordance with the description of JIS K 0068:2001 "Method for measuring moisture in chemical products." The moisture detected in the Karl Fischer measurement was considered to be derived from the OH groups of inorganic particles, and the moisture detected at a temperature of 550°C was considered to be derived from hydrogen-bonded OH groups, and the moisture detected at a temperature of 900°C was considered to be derived from isolated OH groups. The moisture detected in the Karl Fischer measurement is considered to be one water molecule formed by condensation of two OH groups, and the number of OH groups was calculated by the following formula (3). Number of OH groups [pcs / nm 2] = 0.0662 × (water content [ppm]) / (specific surface area of ​​inorganic particles [m 2 / g]) · · · (3)

[0080] [Particle size distribution of inorganic particles] The D50 and D90 of inorganic particles (alumina particles) were measured by the laser diffraction method using a Microtrack MT3300EXII laser particle size distribution measuring device manufactured by Microtrack Bell Co., Ltd. The D50 and D90 were obtained from the particle size distribution measurement results. The inorganic particles to be measured were added to a 0.2 mass% sodium hexametaphosphate solution so that the laser scattering intensity was appropriate, and the inorganic particle dispersion was dispersed for 5 minutes using the built-in ultrasonic of 40 W. The refractive index of the inorganic particles (alumina) was set to 1.76.

[0081] [BET specific surface area of ​​inorganic particles] The specific surface area was measured using a Shimadzu Flowsorb III 2310 specific surface area measuring device, and the nitrogen adsorption BET specific surface area was determined by the single point nitrogen adsorption method according to the method specified in JIS-Z8830 (2013). The measurement conditions were as follows: Carrier gas: Nitrogen / helium mixed gas Filling sample amount: 0.1g Sample pretreatment conditions: 200°C for 20 minutes Nitrogen adsorption temperature: Liquid nitrogen temperature (below -196℃) Nitrogen desorption temperature: room temperature (approximately 20°C)

[0082] [Measurement of the outer edge length L1 of an inorganic particle and the total length L2 of the grain boundary inside the particle] Samples for cross-sectional observation were prepared using inorganic particles (alumina particles) of samples No. 1 to 4. In preparing the samples for cross-sectional observation, the inorganic particles were embedded in resin for cross-sectional observation, and then the resin and inorganic particles were cut with a diamond cutter. Then, Pt was vapor-deposited on the cross-section as a protective film, the cross-section was prepared by Ar ion milling, and the sample was fixed to the SEM sample stage with Cu double-sided tape, and SEM-EBSD measurement was performed without vapor deposition. The observation position was determined so that two or more inorganic particles were completely within the observation area (i.e., two or more inorganic particles did not come into contact with the frame of the observation area). All of the inorganic particles measured were α-alumina particles.

[0083] The following equipment was used for sample preparation and EBSD measurement: ·Equipment used Ion milling device: IM-4000 (manufactured by Hitachi, Ltd.) Ion sputtering device: E-1030 (manufactured by Hitachi, Ltd.) Ultra-high resolution field emission scanning electron microscope: JSM-7800F Prime (manufactured by JEOL Ltd.) Backscattered electron diffraction equipment: Digiview V (TSL)

[0084] The EBSD measurement conditions were as follows: ·Measurement area: 500.0μm×400.0μm Acceleration voltage: 20.0 kV Magnification: x500 ·Vacuum degree: 30Pa

[0085] In the obtained EBSD image, two or more inorganic particles that were not in contact with the frame of the observation area were selected, and the outer edge length L1 of each inorganic particle was averaged using the image processing software Image J (National Institute of Health). The "total grain boundary length L2" is the sum of the grain boundaries contained inside the inorganic particle, and does not include the outer edge of the inorganic particle. The total grain boundary length L2 was calculated by adding the total length of the grain boundaries inside the inorganic particle and the total length of the inner wall of the cavity (if there is a cavity inside the inorganic particle).

[0086] The ratio of the total grain boundary length L2 to the outer edge length L1 (L2 / L1) was expressed as a percentage (%). The more grain boundaries and cavities there are inside the inorganic particle, the higher the value of L2 / L1 (%).

[0087] [Uranium and thorium content in inorganic particles] The uranium content (U amount) and thorium content (Th amount) contained in inorganic particles (alumina particles) were measured as follows. First, the inorganic particles were put into a mixed aqueous solution of sulfuric acid and phosphoric acid, and heated to dissolve the inorganic particles, preparing an aqueous solution. Then, the aqueous solution was contacted with a cyclohexane solution of tributyl phosphate, which is commonly used as an extractant for uranium, to extract the uranium contained in the aqueous solution. Then, the uranium transferred to the aqueous phase by back-extraction by contacting again with pure water was measured by the intensities of U238amu and Th232amu using ICP-MS. A standard solution manufactured by SPEX was used to create a calibration curve.

[0088] [Amount of alpha rays emitted from inorganic particles] The amount of alpha rays emitted from inorganic particles (alumina particles) was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).

[0089] [Preparation of resin composition] Resin compositions were prepared by kneading inorganic particles (alumina particles), resin, etc. (Samples No. 1 to 4). The types of resins used are shown in Table 1, and the blended (added) amounts of inorganic particles are shown in Table 3. In addition, the elastic modulus of the resin not containing inorganic particles was measured when cured, and is shown in the "Elastic Modulus" column of "Resin" in Table 3. Specifically, the resin compositions of Samples No. 1 to 4 were prepared according to the following preparation method. The "resin composition" in Table 3 indicates the resin composition in a cured state.

[0090] (1) Preparation of varnish A 30% by mass mixed solution was prepared by dissolving the resin shown in Table 1 in the solvent shown in Table 1. Furthermore, a curing agent (4,4-diaminodiphenylmethane (manufactured by TCI)) was added in an amount of 0.074% by mass relative to 100% by mass of the mixed solution to prepare a varnish.

[0091] (2) Preparation of inorganic particle / varnish mixture Inorganic particles were added to the obtained varnish, and the mixture was kneaded using a planetary centrifugal mixer (manufactured by Thinky Corporation) to prepare an inorganic particle / varnish mixture.

[0092] (3) Film formation The obtained inorganic particle / varnish mixture was applied onto a PET substrate, and a film was formed using an applicator so that the film thickness after thermal curing would be 150 to 200 μm, thereby obtaining a resin composition before curing.

[0093] (4) Heat curing The obtained resin composition before curing was left to stand at room temperature for 1 hour, then heated at 140°C for 15 minutes, and further vacuum press molded at 140°C for 20 minutes at a pressure of 0.5 MPa using a press molding machine, and then heated at 180°C for 120 minutes at normal pressure to be thermally cured. In this way, cured resin compositions (samples No. 1 to 4) were obtained. In the resin compositions of samples No. 1 to 4, the proportion of solids in the entire resin composition was 95% by volume or more.

[0094] [Table 1]

[0095] Details of the resin types listed in Table 1 are as follows:

[0096] Mesogenic epoxy resin (A) It is a prepolymer obtained by reacting trans-4-{4-(2,3-epoxypropoxy)phenyl}cyclohexyl 4-(2,3-epoxypropoxy)benzoate (an epoxy resin represented by the structural formula below) with 6-hydroxy-2-naphthoic acid.

[0097] [ka]

[0098] Mixture of JP-100 and HP6000 The resin was prepared by mixing JP-100 (manufactured by Nippon Soda Co., Ltd.), an epoxidized polybutadiene, and HP-6000 (manufactured by DIC Co., Ltd.), a naphthalene-based epoxy resin, in a mass ratio of 1:9.

[0099] [Breaking stress, absorbed energy until breakage, correlation coefficient of stress-strain curve until breakage, and elastic modulus of resin composition] The breaking stress, absorbed energy until breaking, correlation coefficient of the stress-strain curve until breaking, and elastic modulus of the resin composition were measured in accordance with JIS K7161 (2014). Specifically, a tensile test was performed under the following conditions, and the obtained stress-strain curve was analyzed and calculated. Test equipment: Autograph AGS-X (Shimadzu Corporation) Load cell: 1kN - Test piece size: 100mm x 10mm Test environment: 22℃ / 59%RH Analysis software: TRAPEZIUMX

[0100] [α-ray dose emitted from resin composition] The amount of α-rays emitted from the resin composition was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas used was PR-10 gas (Ar 90%, CH4 10%).

[0101] [Dimensional change of resin composition when repeatedly heated] The dimensional change of the resin composition when repeatedly heated was evaluated as follows. First, the coefficient of thermal expansion (CTE) was determined in the temperature range of 27° C. to 150° C. by thermomechanical analysis in accordance with JIS K7197. The analysis conditions are shown below. Equipment: TMA7100 (Hitachi High-Tech Science) Measurement mode: Tensile mode - Test piece width: 5mm Chuck distance: 20mm Heating and cooling process: Heat from 20℃ to 200℃ at a rate of 5℃ / min, then cool from 200℃ to 20℃ at a rate of 5℃ / min. -CTE calculation temperature range: 27℃ to 150℃ during heating process Measurement load: 0.05N The above CTE measurement was carried out twice, and the specimen with the smallest CTE change rate calculated from the following formula was evaluated as having the smallest dimensional change when repeatedly heated. CTE change rate (%) = (CTE of first measurement - CTE of second measurement) / (CTE of first measurement) × 100

[0102] Table 2 shows the results of various measurements of the inorganic particles, and Table 3 shows the type (and elastic modulus) of the resin used and the results of various measurements of the resin composition.

[0103] [Table 2]

[0104] [Table 3]

[0105] The measurement results are discussed below. The resin compositions of samples Nos. 1 to 3, which satisfied the requirements of this embodiment, were able to sufficiently suppress the dimensional change when repeatedly heated (i.e., the CTE change rate was 8.4% or less). On the other hand, the resin composition of sample No. 4, which did not satisfy the requirements of this embodiment, had a CTE change rate of 8.5%, and was unable to sufficiently suppress the dimensional change when repeatedly heated.

Claims

1. Contains inorganic particles and a resin, The breaking stress is more than 41.2 MPa, A resin composition having an absorbed energy to break of more than 0.314 MPa.

2. The resin composition according to claim 1, wherein a correlation coefficient when a stress-strain curve up to break is linearly approximated exceeds 0.9765.

3. Alpha radiation dose is 0.022 cph / cm 2 The resin composition according to claim 1 , wherein the molecular weight is less than 1.

0.

4. The resin composition according to claim 1 , wherein the inorganic particles have a strain at break of less than 0.113 in a particle compression test.

5. The resin composition according to claim 1 , wherein the inorganic particles have a breaking strength of less than 1080 MPa in a particle compression test.

6. The resin composition according to claim 1 , wherein the inorganic particles have an absorbed energy until breakage of less than 61.0 MPa in a particle compression test.

7. The resin composition according to claim 1 , wherein the inorganic particles have a ratio of the number of isolated OH groups to the number of hydrogen-bonded OH groups of less than 0.

39.

8. The inorganic particles have an isolated OH group count of 3.1 / nm 2 The resin composition according to claim 1 , wherein the molecular weight is less than 1.

0.

9. The resin composition according to any one of claims 1 to 8 is used. A sheet molding compound having a thickness of 1000 μm or less.

Citation Information

Patent Citations

  • Resin composition, cured product, sealing film, and sealing structure

    JP2020200478A